2019
DOI: 10.6018/analesps.352761
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas del Cuestionario de Experiencias de Recuperación en trabajadores argentinos.

Abstract: Título: Propiedades psicométricas del Cuestionario de Experiencias de Recuperación en trabajadores argentinos. Resumen: El objetivo de este estudio consistió en examinar las propiedades psicométricas del Cuestionario de Experiencias de Recuperación para su uso en Argentina. La muestra estuvo compuesta por 505 trabajadores provenientes del sector público, privado y organizaciones no gubernamentales. Los resultados del análisis factorial confirmatorio evidenciaron que un modelo de cuatro factores ─distanciamient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
4
0
2
Order By: Relevance
“…Although these results converge with the proposal by Sanz-Vergel et al ( 2010), studies carried out in other contexts have confirmed the structure of 16 elements; for example, the Argentine version for public and private sector workers (Trógolo et al, 2020), the Nepali format developed with nurses from university hospitals (Panthee et al, 2020), the version for Spanish university students (Merino-Tejedor et al, 2017) and the version for Japanese employees, although in the latter, a structure adjusted to 3 factors was initially identified, where psychological detachment and relaxation were condensed into a single factor (Shimazu et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although these results converge with the proposal by Sanz-Vergel et al ( 2010), studies carried out in other contexts have confirmed the structure of 16 elements; for example, the Argentine version for public and private sector workers (Trógolo et al, 2020), the Nepali format developed with nurses from university hospitals (Panthee et al, 2020), the version for Spanish university students (Merino-Tejedor et al, 2017) and the version for Japanese employees, although in the latter, a structure adjusted to 3 factors was initially identified, where psychological detachment and relaxation were condensed into a single factor (Shimazu et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…It should be noted that in the initial work by Sonnentag and Fritz (2007) work stress and control over work were considered as contrast variables, identifying the inverse relationship between time pressure and recovery experience; as well as between role ambiguity and situational limitations with psychological detachment and control over free time, and between overtime compliance with psychological detachment and relaxation. In other works, the recovery construct was inversely associated with negative affectivity and exhaustion and was positively associated with vigor, self-regulation, commitment, coping strategies, and certain personality dimensions (Merino-Tejedor et al, 2017;Trógolo et al, 2020).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…37, nº 1 (january) that they see are rewarded (Chatman & O'Reilly, 2016;Ehrhart et al, 2014;Loh et al, 2019;Schneider et al, 2013). OC is theorised as a group construct which represents the collective perceptions of the work environment, assessed individually and based on self-reporting by which the employee assesses his/her own perceptions of these aspects (Menéndez et al, 2017;Trógolo et al, 2019). According to the ALS model, the OC is influenced by the culture of the or-ganization and the support given by its leader, which in turn moderates individual perceptions and exercises reciprocal influence on intersubjective processes.…”
Section: Introductionmentioning
confidence: 99%